Environmental Assessment of Austrian Organic Dairy Farms With Closed Regional Production Cycles in a Less Favorable Production Area - Grassauer, Florian; Herndl, Markus; Iten, Laura; Gaillard, Gérard (Frontiers in Sustainable Food Systems, 2022)
Extensive dairy production in less favorable production areas has a long tradition in Austria. Nevertheless, dairy production also contributes considerable environmental impacts (EIs), e.g., greenhouse gas emissions, nutrient losses, and land use. Therefore, 20 organic dairy farms located in the Lungau region in Austria were assessed concerning their EIs via life cycle assessment (LCA). Cumulative exergy demand (CExD), normalized eutrophication potential (EP), aquatic ecotoxicity potential (AE), and global warming potential (GWP) were considered as impact categories to describe the farms' EIs. The farms were part of a pilot project aiming to produce high-quality dairy products and keep production cycles closed within the project region. Consequently, the purchase of key off-farm resources was only possible within the project region. We adapted existing life cycle inventories to account for those regional resource purchases. Subsequently, the EIs of the 20 farms were related to the functional units (FUs) of 1 kg energy corrected milk (ECM) and 1 ha agricultural area for milk production and compared to a representative model dairy farm (MDF) that was created based on statistical data and average production values of organic Austrian dairy farms. Compared to the MDF, results show an approximately 58 % lower EP per ha and 44 % per kg ECM of the Lungau farms. Further, the CExD per ha was about 24 % lower due to a lower use of resources caused by the lower production intensity of the Lungau farms. Regarding GWP, Lungau farms are favorable considering 1 ha as the FU, whereas the MDF seems advantageous if 1 kg ECM is used as the FU. However, caused by a high variation of purchased roughage and the lower production intensity, the Lungau farms cause higher AE, regardless of the FU. Overall, we identified three principal production parameters determining the environmental performance of milk production in a closed production cycle in a less favorable area, namely (1) the stocking rate, (2) the fed concentrate, and (3) the purchased roughage. Using those inputs at moderate intensity, the extensively managed Lungau farms can competitively contribute to producing food, thus highlighting the importance of site-adapted agriculture.